2021
DOI: 10.1021/acssuschemeng.1c02472
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Nanoparticle-Decorated Cobalt–Molybdenum Bimetal Oxides Embedded in Flower-like N-Doped Carbon as a Durable and Efficient Electrocatalyst for Oxygen Evolution Reaction

Abstract: The development of high-efficiency and cost-efficient oxygen evolution reaction (OER) catalysts is a core issue in the sector of water electrolysis. Cobalt–molybdenum bimetal oxide (Co2Mo3O8), as a kind of non-noble transition-metal oxides, is broadly employed as a good OER catalyst due to its abundant active sites. However, the relatively low conductivity of Co2Mo3O8 limits further improvement in its electrocatalytic performance. Herein, the cobalt nanoparticle-modified Co2Mo3O8 flakes are embedded into the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…33 However, the peak of graphitic carbon is not shown in the PXRD pattern because of the high crystallinity of metal phosphide. 34 The BET surface area and pore diameter of 3D Cu-MOF and Cu 3 P/Cu@NC heterostructure were measured through the N 2 adsorption−desorption isotherm having surface areas of 12.88 and 139.8 m 2 g −1 and pore diameters of 1.86 and 1.91 nm, respectively, as shown in Figure S1. After phosphorization, the total pore diameter and BET surface area of the Cu 3 P/ Cu@NC heterostructure was increased as compared to Cu-MOF due to the increased carbon content of materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 However, the peak of graphitic carbon is not shown in the PXRD pattern because of the high crystallinity of metal phosphide. 34 The BET surface area and pore diameter of 3D Cu-MOF and Cu 3 P/Cu@NC heterostructure were measured through the N 2 adsorption−desorption isotherm having surface areas of 12.88 and 139.8 m 2 g −1 and pore diameters of 1.86 and 1.91 nm, respectively, as shown in Figure S1. After phosphorization, the total pore diameter and BET surface area of the Cu 3 P/ Cu@NC heterostructure was increased as compared to Cu-MOF due to the increased carbon content of materials.…”
Section: Resultsmentioning
confidence: 99%
“…65–9743) . However, the peak of graphitic carbon is not shown in the PXRD pattern because of the high crystallinity of metal phosphide …”
Section: Resultsmentioning
confidence: 99%
“…To better adapt to the practical applications, low cost, environmental friendliness and other problems cannot be ignored. [197][198][199][200][201][202][203][204] We need to develop simple, universal and large-scale production techniques to meet these needs. So far, there is few reports about the synthesis route for mesoporous carbon-based films by one step.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we notice a family of honeycomb-like ABMo 3 O 8 with high conductivity. Crystallographically, ABMo 3 O 8 has a hexagonal lattice structure alternating AB layers and Mo layers, belonging to the P 63 mc space group. Within the AB layer, A and B represent 3d TM cations such as Mn, Fe, Co, Ni, etc. and occupy the coordination of O h and T d , respectively.…”
mentioning
confidence: 92%
“…Although Liu’s group identified that the T d Co was an active site through theoretical calculations, there is still no experimental evidence to support this conclusion . Furthermore, most existing studies have focused on heterojunctions of metal/metal oxide and Co 2 Mo 3 O 8 , limiting the evaluation of the intrinsic activity of Co 2 Mo 3 O 8 . Therefore, a clear consensus on the fundamental understanding of their structure–property relationships has yet to be reached.…”
mentioning
confidence: 99%